2013
DOI: 10.1108/ijchm-dec-2011-0223
|View full text |Cite
|
Sign up to set email alerts
|

Transformational vs transactional leadership: which is better?

Abstract: Purpose – This research examines the relationships among transformational/transactional leadership styles (TFLs/TSLs), organizational justice, trust, organizational commitment, and organizational citizenship behaviors (OCBs) in the context of international tourist hotels in Taipei. The purpose of this paper is to establish a comprehensive model of TFLs/TSLs in human resource management and to figure out which is the better leadership style in regards to the hospitality industry. Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 55 publications
5
64
0
4
Order By: Relevance
“…There is no consensus on these results though, as other studies have concluded that transactional leadership has greater predictive power on the OCB when compared to transformational leadership (Suliman & Obaidly, 2013;Whittington et al, 2009). Other studies have observed that neither transactional nor transformational leadership directly affect the OCB (Dai, Dai, Chen, & Wu, 2013). These contradictory results can be due to the fact that these different studies were conducted in distinct cultural contexts, as earlier evidences indicate that the influence of these two leadership styles on the OCB is moderated by cultural factors (Cavazotte et al, 2014;Euwema et al, 2007).…”
Section: Transactional Leadership Transformational Leadership and Ormentioning
confidence: 92%
“…There is no consensus on these results though, as other studies have concluded that transactional leadership has greater predictive power on the OCB when compared to transformational leadership (Suliman & Obaidly, 2013;Whittington et al, 2009). Other studies have observed that neither transactional nor transformational leadership directly affect the OCB (Dai, Dai, Chen, & Wu, 2013). These contradictory results can be due to the fact that these different studies were conducted in distinct cultural contexts, as earlier evidences indicate that the influence of these two leadership styles on the OCB is moderated by cultural factors (Cavazotte et al, 2014;Euwema et al, 2007).…”
Section: Transactional Leadership Transformational Leadership and Ormentioning
confidence: 92%
“…It also reflects the negative effect of transactional leadership on workplace deviance behavior from another perspective. That is to say, employees are more likely to exhibit citizenship behavior under their approved contractual relationship, and form workplace deviance behavior under their unapproved contractual relationship [ 51 ]. Therefore, transactional leadership concentrates on task-oriented management, which has a great impact on the specific behavior of employees and can supervise and restrain their workplace deviance behaviors.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…It is a more passive leadership style that calls for oversight of deviations, mistakes and errors and rectifying the problems as they arise (Obiwuru, Okwu, Akpa & Nwankwere, 2011). This leadership type limits the development of the innovative and creative skills of employees and prevents them and the organization from growing (Dai, Dai, Chen & Wu, 2013).…”
Section: Transactional Leadershipmentioning
confidence: 99%